A catalyst for catalytic cracking to produce light olefins, and its preparation method and application

By developing a MFI structural molecular screen catalyst with loading and phosphorus, the problem of lack of activity and selectivity in the catalyst in catalytic cracking process is solved, and low energy consumption, high activity and high -selective production of low -carbon olefins are achieved.

CN116408136BActive Publication Date: 2025-01-24PETROCHINA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111646234.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-01-24
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The existing catalysts have poor catalytic cracking activity in the catalytic cracking process, making it difficult to effectively crack complex raw oils, and it is difficult to significantly improve the selectivity of low-carbon olefins, resulting in high raw material costs.

Method used

Develop a catalyst, which includes MFI structural molecular sieves and 镧 and phosphorus loaded in MFI structural molecular sieves. It has a two -segment medium distribution and appropriate acidic site. sex.

Benefits of technology

Without increasing the cost of raw materials, the production of low -energy, high activity, and high -selective production of low -carbon olefins is achieved, reducing the regeneration frequency of catalysts and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116408136B_ABST
    Figure CN116408136B_ABST
Patent Text Reader

Abstract

The present invention provides a catalyst for catalytic cracking and producing light olefins, and a preparation method and application thereof, wherein the catalyst comprises an MFI structure molecular sieve and lanthanum and phosphorus loaded on the MFI structure molecular sieve, wherein the mass percentage of the lanthanum in the catalyst is 0.5-1.5%, and the mass percentage of the phosphorus in the catalyst is 0.5-0.9%; the catalyst comprises a first mesopore distribution of 2-4 nm and a second mesopore distribution of 7-20 nm. The catalyst can realize the production of light olefins with low energy consumption, low cost, high activity and high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst, in particular to a catalyst for producing light olefins through catalytic cracking and a preparation method and application thereof, belonging to the technical field of catalysts. Background Art

[0002] Low-carbon olefins represented by ethylene and propylene are important chemical raw materials and occupy an important position in the national economy. With the rapid expansion of demand for downstream derivatives of ethylene and propylene, the overall demand for ethylene and propylene in my country has shown a steady growth trend. Therefore, the development of new technologies for the production of low-carbon olefins is an inevitable trend in the development of my country's energy industry at this stage.

[0003] At present, the production of low-carbon olefins in my country presents a diversified structure, such as steam cracking, coal-to-olefins (CTO), methanol-to-olefins (MTO), propane dehydrogenation (PDH), etc. In terms of plant capacity and scale, naphtha steam cracking is still the main one. The oil route represented by naphtha steam cracking has a stable source of raw materials, and because the cracking unit has a good yield of ethylene and propylene, and co-produces butadiene, benzene, toluene, xylene, C5, C9 and other basic chemical raw materials, especially under the situation of low oil prices, its economic efficiency is more advantageous. However, with the increasingly stringent national energy conservation, emission reduction and environmental protection policies, its further development has been greatly restricted.

[0004] Non-petroleum routes represented by MTO have become an important part of my country's low-carbon olefin production, but the profit of MTO is restricted by the raw material methanol. In recent years, the price of methanol has fluctuated greatly, and its price can reach more than 3,000 yuan / ton, which makes the economic benefits of the MTO industry not ideal. It often occurs that the operating rate is low or even production is stagnant due to poor profits.

[0005] For many years, people have been exploring technical countermeasures that can significantly reduce energy consumption and equipment investment, and reduce environmental pollution compared to traditional thermal cracking technology. Among them, catalytic cracking can reduce the reaction temperature and obtain a higher yield of low-carbon olefins under milder conditions than thermal cracking, which has attracted widespread attention. However, catalytic cracking is still a highly endothermic reaction process, requiring high energy consumption, and its system still has problems such as heating and water supply.

[0006] Compared with catalytic cracking, although MTO is a highly exothermic reaction, the product distribution and process conditions of the two are similar. Therefore, coupling the two process technologies has the characteristics of reducing the heat load of the reaction system, reducing production energy consumption, and saving or reducing the amount of water vapor in the system. In addition, this coupling technology can adapt to the cost increase caused by the fluctuation of cracking raw material prices. By allocating cracking raw materials, avoiding industry risks, and achieving the coordinated development of petrochemicals and coal chemical industry, it has great development potential. However, at present, the core restricting the development of coupling process is the catalyst. On the one hand, the catalytic cracking activity of the existing catalysts used in the coupling process is poor, especially for some complex raw oils, it is difficult to achieve the cracking of large molecules and cyclic molecules; on the other hand, these catalysts are difficult to significantly improve the selectivity of light olefins, and often require increasing the use of methanol to increase the yield of light olefins, which in turn makes the cost of raw materials high.

[0007] Therefore, how to achieve the preparation of light olefins through a coupling process with low cost, low energy consumption, high activity and high selectivity is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0008] The present invention provides a catalyst for producing light olefins by catalytic cracking. The catalyst has a special mesoporous distribution and loaded elements, can be used as a catalyst in a coupling process without increasing the cost of raw materials, and ultimately achieves the production of light olefins with low energy consumption, high activity and high selectivity.

[0009] The present invention also provides a method for preparing the above catalyst. The catalyst prepared by the method can achieve the production of light olefins at low cost, low energy consumption, high activity and high selectivity.

[0010] The present invention also provides a composite catalyst, which comprises the above catalyst and has a catalytic effect similar to that of the above catalyst.

[0011] The present invention also provides a method for producing light olefins, which can realize the production of light olefins with low cost, low energy consumption, high activity and high selectivity.

[0012] The present invention provides a catalyst for producing low-carbon olefins by catalytic cracking, the catalyst comprising an MFI structure molecular sieve and lanthanum and phosphorus loaded on the MFI structure molecular sieve, wherein the mass percentage of the lanthanum in the catalyst is 0.5-1.5%, and the mass percentage of the phosphorus in the catalyst is 0.5-0.9%;

[0013] The catalyst includes a first mesopore distribution of 2-4 nm and a second mesopore distribution of 7-20 nm.

[0014] The catalyst as described above, wherein the mesopore volume of the catalyst is 0.08-0.20 cm 3 / g.

[0015] The catalyst as described above, wherein the micropore volume of the catalyst is 0.08-0.15cm 3 / g.

[0016] The present invention also provides a method for preparing the catalyst for producing light olefins by catalytic cracking as described in any one of the above, comprising the following steps:

[0017] 1) a gel system including a silicon source, an aluminum source, a polymer stabilizer, a template, deionized water, and a sodium hydroxide aqueous solution is sequentially subjected to a crystallization treatment, a first calcination treatment, an ammonium ion exchange treatment, and a second calcination treatment to obtain a molecular sieve; the mass of the polymer stabilizer is 5-20% of the mass of the silicon source;

[0018] 2) After the molecular sieve is subjected to lanthanum element loading treatment, an intermediate catalyst is obtained;

[0019] 3) subjecting the intermediate catalyst to a phosphorus loading treatment, followed by a drying treatment and a third calcination treatment, to obtain the catalyst for catalytic cracking to produce light olefins;

[0020] The loading treatment of the lanthanum element comprises impregnating the molecular sieve with a lanthanum salt solution, and the impregnation amount of the lanthanum salt solution is 0.2-0.5 ml / g;

[0021] The phosphorus loading treatment includes impregnating the intermediate catalyst with a phosphorus salt solution, and the impregnation amount of the phosphorus salt solution is 0.2-0.5 ml / g.

[0022] In the preparation method as described above, the molar ratio of the silicon source, the aluminum source, sodium hydroxide, the template and deionized water is 100:(1.11-1.82):(5-12.5):(5-10):(1000-3000).

[0023] The preparation method as described above, wherein the crystallization treatment includes a first crystallization treatment and a second crystallization treatment performed sequentially; wherein the temperature of the first crystallization treatment is 120-140°C, the time is 8-16h, and the temperature of the second crystallization treatment is 170-200°C, the time is 28-40h.

[0024] In the preparation method as described above, the polymer stabilizer is selected from at least one of polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 6000.

[0025] The present invention provides a composite catalyst, which comprises any one of the above-mentioned catalysts for producing light olefins by catalytic cracking, and the mass percentage of the catalyst for producing light olefins by catalytic cracking in the composite catalyst is not less than 42%.

[0026] The present invention provides a method for producing low-carbon olefins, which comprises catalytically cracking a raw material system using any one of the above-mentioned catalysts and / or the above-mentioned composite catalyst at 560-640° C. and normal pressure.

[0027] The production method as described above, wherein the raw material system comprises a first raw material and a second raw material, the first raw material is selected from methanol, the second raw material is selected from at least one of petroleum products with a distillation range of 40 to 220° C., the mass ratio of the first raw material to the second raw material is (0-2):1, and the mass space velocity of the second raw material is 1-5h -1 .

[0028] The catalyst for producing low-carbon olefins by catalytic cracking of the present invention can be used for the production of low-carbon olefins, and is particularly suitable for the coupling process of MTO and thermal cracking. The catalyst has a dual-segment mesoporous distribution, which is conducive to the diffusion of raw materials inside it, and can achieve excellent catalytic activity and low-carbon selectivity at a lower catalytic temperature without increasing the methanol raw material. In addition, the quantitative loading of the special elements of the catalyst can make the catalyst have suitable acidity, thereby further improving the catalytic activity and low-carbon selectivity of the catalyst by inhibiting the carbon deposition of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD spectra of the catalysts prepared in Comparative Example 1 and Example 1 of the present invention;

[0030] Figure 2 NH3-TPD spectra of the molecular sieve catalysts prepared in Comparative Example 1, Comparative Example 4 and Example 1 of the present invention;

[0031] Figure 3 This is the nitrogen adsorption-desorption curve of the molecular sieve catalyst prepared in Example 1 of the present invention;

[0032] Figure 4 This is the DFT model pore size distribution curve of the molecular sieve catalyst prepared in Example 1. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The first aspect of the present invention provides a catalyst for catalytic cracking to produce light olefins, the catalyst comprising an MFI structured molecular sieve and lanthanum and phosphorus loaded on the MFI structured molecular sieve, wherein the mass percentage of the lanthanum in the catalyst is 0.5-1.5%, and the mass percentage of the phosphorus in the catalyst is 0.5-0.9%; the catalyst comprises a first mesopore distribution of 2-4 nm and a second mesopore distribution of 7-20 nm.

[0035] The catalyst of the present invention is used for catalytic cracking to produce light olefins (mainly ethylene and propylene), and is particularly suitable for catalytic cracking of a coupled raw material system of methanol and petroleum products (such as naphtha) to produce light olefins.

[0036] In terms of composition, the catalyst comprises an MFI structure molecular sieve, and lanthanum and phosphorus loaded on the MFI structure molecular sieve. The inventors found that when the mass percentage of lanthanum in the catalyst is 0.5-1.5%, and the mass percentage of phosphorus in the catalyst is 0.5-0.9%, the catalyst has a suitable acid site (the temperature of the weak acid site is 170-210°C, and the temperature of the strong acid site is 390-410°C), and the acid site is conducive to inhibiting the carbon deposition phenomenon of the catalyst during use, thereby ensuring the catalytic activity and light olefin selectivity of the catalyst, reducing the regeneration frequency of the catalyst, and extending the service life of the catalyst, and finally achieving a high conversion rate of the raw materials and a high yield of the light olefins at a lower raw material cost.

[0037] In terms of structure, the catalyst of the present invention has a dual-segment mesopore distribution, specifically a first mesopore distribution of 2-4 nm and a second mesopore distribution of 7-20 nm. This mesopore distribution is conducive to the diffusion of raw materials inside the catalyst, especially to the entry and diffusion of macromolecules of cycloalkanes into the catalyst, and significantly improves the catalytic activity and the yield of light olefins by avoiding the aggregation of raw materials on the catalyst surface and expanding the contact area between the raw materials and the catalyst.

[0038] Therefore, the catalyst of the present invention having the above-mentioned composition and structure is conducive to achieving an improvement in the raw material conversion rate and the yield of light olefins. In the specific cracking catalytic process, there is no need to promote the catalytic activity or the generation of light olefins by means of increasing the reaction temperature, increasing the amount of water vapor, etc., and it also has a significant effect on reducing costs and energy consumption.

[0039] Furthermore, the mesopore volume of the catalyst of the present invention is 0.08-0.20 cm 3 / g.

[0040] In addition, the catalyst of the present invention also has micropores, and the pore volume of the micropores is 0.08-0.15cm 3 / g.

[0041] When the catalyst of the present invention has the above-mentioned mesopore volume and / or micropore volume, the mesopores and micropores are not easy to collapse and damage even in a hydrothermal environment with a relatively high temperature, and the hydrothermal stability is good, thereby helping to ensure the catalytic stability of the catalyst and extend its service life.

[0042] The catalyst of the present invention realizes the efficient preparation of low-carbon olefins at low cost and low energy consumption through its own special composition and structure, and the catalyst is particularly suitable for the coupling raw materials of methanol and petroleum products.

[0043] The second aspect of the present invention provides a method for preparing the catalyst described in any one of the above items, comprising the following steps:

[0044] 1) a gel system comprising a silicon source, an aluminum source, a polymer stabilizer, a template, deionized water, and a sodium hydroxide aqueous solution is sequentially subjected to a crystallization treatment, a first calcination treatment, an ammonium ion exchange treatment, and a second calcination treatment to obtain a molecular sieve; the mass of the polymer stabilizer is 5-20% of the mass of the silicon source;

[0045] 2) After the molecular sieve is subjected to lanthanum element loading treatment, an intermediate catalyst is obtained;

[0046] 3) performing a phosphorus loading treatment on the intermediate catalyst, followed by a drying treatment and a third calcination treatment in sequence to obtain the catalyst for catalytic cracking to produce light olefins;

[0047] The loading treatment of the lanthanum element comprises impregnating the molecular sieve with a lanthanum salt solution, and the impregnation amount of the lanthanum salt solution is 0.2-0.5 ml / g;

[0048] The phosphorus loading treatment includes impregnating the intermediate catalyst with a phosphorus salt solution, and the impregnation amount of the phosphorus salt solution is 0.2-0.5 ml / g.

[0049] The preparation method of the catalyst of the present invention mainly includes three steps, namely the preparation of molecular sieve, the loading of lanthanum element and the loading of phosphorus element.

[0050] The present invention does not limit the preparation method of the gel system in step 1). For example, the gel system can be obtained by first mixing the silicon source, aluminum source, polymer stabilizer, template agent, and deionized water and stirring them thoroughly, then adding sodium hydroxide aqueous solution and stirring for 2-4 hours.

[0051] The addition of the polymer stabilizer helps to evenly disperse the silicon source and the aluminum source in the gel system, which not only reduces the generation of impurity crystals, but also helps to introduce mesopores and form a mesopore distribution of the catalyst in the subsequent crystallization process. Specifically, the mass of the polymer stabilizer is 5-20% of the mass of the silicon source.

[0052] The silicon source, aluminum source, and template agent can be any of the commonly used raw materials in the art, and the present invention does not specifically limit them. For example, the silicon source is selected from at least one of silica sol, macroporous silica gel, white carbon black, and tetraethyl orthosilicate; the aluminum source is selected from at least one of sodium aluminate, sodium metaaluminate, aluminum chloride, aluminum nitrate, aluminum isopropoxide, aluminum hydroxide, and aluminum sulfate; and the template agent is selected from at least one of tetrapropylammonium hydroxide, hexamethylenediamine, and tetrapropylammonium bromide, preferably tetrapropylammonium bromide.

[0053] In one embodiment, the polymer stabilizer is selected from at least one of polyethylene glycol 2000, polyethylene glycol 4000, and polyethylene glycol 6000.

[0054] After the gel system is prepared, the gel system is sequentially subjected to crystallization treatment, a first calcination treatment, an ammonium ion exchange treatment, and a second calcination treatment to prepare a molecular sieve having an MFI structure.

[0055] Subsequently, the molecular sieve is subjected to a loading treatment of lanthanum to obtain an intermediate catalyst. Specifically, the loading treatment of lanthanum includes impregnating the molecular sieve with a lanthanum salt solution. The present invention does not specifically limit the lanthanum salt, for example, it can be at least one of lanthanum chloride, lanthanum nitrate, and lanthanum sulfate solution.

[0056] Finally, the intermediate catalyst is subjected to a phosphorus loading treatment, and then dried to a constant weight and subjected to a third calcination treatment to obtain the catalyst of the present invention. Specifically, the phosphorus loading treatment includes impregnating the molecular sieve with a phosphate salt solution. The present invention does not specifically limit the phosphate salt, for example, it can be at least one of phosphoric acid, ammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate.

[0057] It should be noted that the present invention does not use equal volume impregnation when performing the impregnation treatment of the lanthanum salt solution and the phosphate salt solution, but uses a moisture absorption method to complete the impregnation (stirring or standing for 8-24 hours). Specifically, the moisture absorption method refers to using only a very small volume of impregnation solution to stir or stand the molecular sieve and the intermediate catalyst for 8-24 hours, wherein the impregnation amount of the lanthanum salt solution is 0.2-0.5ml / g, that is, 0.2-0.5ml of lanthanum salt solution is used for impregnation per gram of molecular sieve to prepare the intermediate catalyst; the impregnation amount of the phosphate salt solution is 0.2-0.5ml / g, that is, 0.2-0.5ml of phosphate salt solution is used for impregnation per gram of intermediate catalyst to prepare the catalyst. The inventors found that this moisture absorption impregnation method can effectively prevent the modified elements from being enriched on the surface of the molecular sieve, allowing more modified elements to enter the interior to form more active centers, so that a small amount of modified elements (the mass percentage of lanthanum in the catalyst is 0.5-1.5%, and the mass percentage of phosphorus in the catalyst is 0.5-0.9%) is finally used to achieve efficient loading modification of the molecular sieve, so that the catalyst can still have excellent catalytic activity when it has a lower content of modified elements, and the economic benefits of catalytic cracking to produce light olefins are improved by reducing the production cost of the catalyst. It can be understood that the concentrations of the lanthanum salt solution and the phosphate salt solution are determined according to the target loading amount of the lanthanum element and the phosphorus element.

[0058] In a specific embodiment, in step 1), the molar ratio of silicon source, aluminum source, sodium hydroxide, template and deionized water is 100: (1.11-1.82): (5-12.5): (5-10): (1000-3000). When the gel system is mixed with raw materials according to this ratio, it helps to further improve the catalytic activity. Among them, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the sodium hydroxide is calculated as Na2O, that is, the molar ratio of SiO2, Al2O3, Na2O, template and deionized water is 100: (1.11-1.82): (5-12.5): (5-10): (1000-3000).

[0059] In the process of preparing molecular sieves using the gel system as a starting material, the crystallization treatment and the ammonium ion exchange treatment can be carried out in a manner commonly used in the art.

[0060] Furthermore, when the crystallization treatment of the present invention includes a first crystallization treatment and a second crystallization treatment performed sequentially, and the temperature of the first crystallization treatment is 120-140°C, the time is 8-16h, and the temperature of the second crystallization treatment is 170-200°C, and the time is 28-40h, it helps to further optimize the mesopore volume and micropore volume of the dual-segment mesopore distribution.

[0061] The process of performing amine ion exchange treatment refers to using an ammonium salt solution to exchange the product after the crystallization treatment, wherein the ammonium salt is selected from at least one of ammonium chloride, ammonium sulfate, ammonium nitrate, and ammonium carbonate solution. In order to ensure the efficient implementation of the ammonium ion exchange treatment, an ammonium salt solution with an ion molar concentration of 1-2 mol / L can be used for multiple exchange treatments. Further, 5-20 ml of ammonium salt solution is used for each ion exchange per gram of the product after the crystallization treatment, and the temperature of each ion exchange is 50-80° C., and the time is 1-4 hours, and finally a molecular sieve with a Na2O mass content of less than 0.2% is obtained.

[0062] It can be understood that the preparation process of the catalyst also includes drying and calcining treatments.

[0063] Specifically, in the preparation method of the present invention, after the crystallization treatment is completed, the system after the crystallization treatment is washed, dried and subjected to the first calcination treatment in sequence, and then subjected to the ammonium ion exchange treatment. The drying temperature is 80-120°C for 3-12h; the first calcination treatment temperature is 550-600°C for 4-6h, and the heating rate is 0.5-2°C / min.

[0064] After the ammonium ion exchange treatment is completed, the system after the ammonium ion exchange treatment is washed, dried and subjected to a second calcination treatment in sequence to obtain a molecular sieve, wherein the drying temperature is 80-120°C for 3-12 hours, the second calcination temperature is 550-600°C for 4-6 hours, and the heating rate is 0.5-2°C / min.

[0065] After the loading of the lanthanum salt solution is completed, the loaded system is dried at 80-120° C. to a constant weight to obtain an intermediate catalyst.

[0066] After the loading of the phosphate solution is completed, the loading system is dried at 80-120° C. to a constant weight, and then subjected to a third calcination treatment at 550-600° C. (heating rate 0.5-2° C. / min) for 4-6 hours to obtain a catalyst.

[0067] It should be noted here that, unless otherwise specified, the salt solutions in the present invention are all aqueous salt solutions.

[0068] The third aspect of the present invention further provides a composite catalyst, which comprises the catalyst of the first aspect, and the mass percentage of the catalyst in the composite catalyst is not less than 42%.

[0069] In addition to the above-mentioned catalyst, the composite catalyst may also include other components such as a binder, an inert carrier, and the like.

[0070] The composite catalyst of the present invention, because it includes the above catalyst, can realize the efficient preparation of low-carbon olefins at low cost and low energy consumption. The composite catalyst is particularly suitable for coupling raw materials of methanol and petroleum products.

[0071] The fourth aspect of the present invention provides a method for producing low-carbon olefins. Specifically, the raw material system is catalytically cracked using the catalyst of the first aspect or the composite catalyst of the third aspect at 560-640°C and normal pressure.

[0072] Since the production method uses the catalyst described in the first aspect and / or the composite catalyst described in the third aspect to catalyze the cracking of the raw material system, it is possible to achieve efficient cracking of the raw material system at a relatively low temperature and normal pressure, and ultimately achieve the production of light olefins with low energy consumption, low cost and high yield.

[0073] Furthermore, the raw material system of the production method is a coupled raw material system. The raw material system includes a first raw material and a second raw material, the first raw material is selected from methanol, the second raw material is selected from at least one of petroleum products with a distillation range of 40 to 220°C, the mass ratio of the first raw material to the second raw material is (0-2):1, and the mass space velocity of the second raw material is 1-5h -1 .

[0074] Furthermore, the petroleum product with a distillation range of 40-200° C. is, for example, naphtha and hydrogenated gasoline.

[0075] Hereinafter, the catalyst of the present invention will be described in detail through specific examples.

[0076] Example 1

[0077] The catalyst of this embodiment is prepared according to the following method:

[0078] 1) Take 43.30g silica sol (SiO2 mass content 30%, the same below) and dissolve it in 50.00g deionized water, stir it evenly, and then add 0.65g sodium aluminate; after the sodium aluminate is dissolved, add 4.19g tetrapropylammonium bromide template SDA (mass content 99%, the same below) and 2.10g polyethylene glycol 6000; after the template is fully dissolved, slowly add the pre-prepared sodium hydroxide solution (1.38g sodium hydroxide (mass content 96%, the same below) and 28g deionized water) dropwise to form a gel with a material ratio of 100SiO2:1.21Al2O3:7.6Na2O:7.2SDA:2780H2O, and continue stirring at room temperature for 2h;

[0079] The gel was transferred to a crystallization kettle for crystallization at a temperature of 140°C. After maintaining for 12 hours, the crystallization temperature was raised to 180°C and maintained for 32 hours. The crystallized product was washed, dried at 110°C for 5 hours, and calcined at 550°C for 6 hours at a calcination heating rate of 1°C / min to obtain a sodium molecular sieve.

[0080] The sodium molecular sieve was placed in a 1mol / L ammonium nitrate solution, with an ammonium solution dosage of 10ml (ammonium solution) / g (sodium molecular sieve), and stirred in a water bath at 80°C for 2h. The ammonium ion exchange product was centrifuged and washed to complete a single ammonium ion exchange; the ammonium ion exchange was continued, and the above steps were repeated for a total of three ammonium ion exchanges; the sample after ammonium ion exchange was dried at 80°C for 12h, and then calcined at 550°C for 6h, with a calcination heating rate of 1°C / min, to obtain the molecular sieve HY-1.

[0081] 2) Take 5g of the above HY-1 sample and place it in a 20ml beaker, add 2.5ml of a solution in which 0.24g of lanthanum nitrate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and place the sample at 120°C to dry until constant weight. Then, crush the dried sample in a beaker, add 2.5ml of a solution in which 0.30g of ammonium phosphate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and place the sample at 120°C to dry until constant weight; then, calcine the dried sample at 550°C for 6h, with a calcination heating rate of 1°C / min, to obtain the catalyst SS-1 of this embodiment, with a lanthanum loading of 1.5% and a phosphorus loading of 0.9%.

[0082] Example 2

[0083] The catalyst of this embodiment is prepared according to the following method:

[0084] 1) 15.32 g of coarse-porous silica gel (98% by mass SiO2) powder was placed in 80.00 g of deionized water, stirred evenly, and then 0.45 g of aluminum hydroxide was added; after the aluminum hydroxide was dissolved, 20.33 g of tetrapropylammonium hydroxide template SDA (mass concentration 25%) and 3.06 g of polyethylene glycol 4000 were added; after the template was fully dissolved, a pre-prepared sodium hydroxide solution (1.04 g of sodium hydroxide and 39.81 g of deionized water) was slowly added dropwise to form a gel with a material ratio of 100 SiO2: 1.11 Al2O3: 5 Na2O: 10 SDA: 3000 H2O, and stirring was continued at room temperature for 4 h;

[0085] The gel was transferred to a crystallization kettle for crystallization at a temperature of 120°C for 16 hours, and then the crystallization temperature was raised to 170°C for 40 hours. The crystallized product was washed, dried at 80°C for 12 hours, and calcined at 600°C for 4 hours at a calcination heating rate of 0.5°C / min to obtain a sodium molecular sieve;

[0086] The sodium molecular sieve was placed in a 2mol / L ammonium chloride solution, with the amount of ammonium solution being 5ml (ammonium solution) / g (sodium molecular sieve), and stirred in a water bath at 50°C for 4h. The ammonium ion exchange product was centrifuged and washed to complete a single ammonium ion exchange; the ammonium ion exchange was continued, and the above steps were repeated for a total of four ammonium ion exchanges; the sample after ammonium ion exchange was dried at 120°C for 3h, and then calcined at 600°C for 4h, with a calcination heating rate of 0.5°C / min, to obtain the molecular sieve HY-2.

[0087] 2) Take 5g of the above HY-2 sample and place it in a 20ml beaker, add 1.0ml of a solution in which 0.08g of lanthanum nitrate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 24h; remove the plastic wrap, and dry the sample at 80°C to constant weight. Then, crush the dried sample in a beaker, add 1.0ml of a solution in which 0.11g of diammonium hydrogen phosphate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 24h; remove the plastic wrap, and dry the sample at 80°C to constant weight; then, calcine the dried sample at 600°C for 4h, with a calcination heating rate of 0.5°C / min, to obtain the catalyst SS-2 of this embodiment, with a lanthanum loading of 0.5% and a phosphorus loading of 0.5%.

[0088] Example 3

[0089] The catalyst of this embodiment is prepared according to the following method:

[0090] 1) 34.66 g of white carbon black powder (98% by mass of SiO2) was placed in 50.00 g of deionized water, stirred evenly, and then 2.56 g of sodium aluminate was added; after the sodium aluminate was dissolved, 22.99 g of tetrapropylammonium hydroxide template SDA (mass concentration 25%) and 1.74 g of polyethylene glycol 2000 were added; after the template was fully dissolved, a pre-prepared sodium hydroxide solution (5.89 g of sodium hydroxide and 34.61 g of deionized water) was slowly added dropwise to form a gel with a material ratio of 100 SiO2: 1.82 Al2O3: 12.5 Na2O: 5 SDA: 1000 H2O, and stirring was continued at room temperature for 1 hour;

[0091] The gel was transferred to a crystallization kettle for crystallization at a temperature of 130°C for 8 hours, and then the crystallization temperature was raised to 200°C for 28 hours. The crystallized product was washed, dried at 120°C for 3 hours, and calcined at 580°C for 5 hours at a calcination heating rate of 2°C / min to obtain a sodium molecular sieve;

[0092] The sodium molecular sieve was placed in a 1mol / L ammonium sulfate solution, with an ammonium solution dosage of 20ml (ammonium solution) / g (sodium molecular sieve), and stirred in a water bath at 70°C for 1h. The ammonium ion exchange product was centrifuged and washed to complete a single ammonium ion exchange; the ammonium ion exchange was continued, and the above steps were repeated for a total of five ammonium ion exchanges; the sample after ammonium ion exchange was dried at 110°C for 6h, and then calcined at 580°C for 5h, with a calcination heating rate of 2°C / min, to obtain the molecular sieve HY-3.

[0093] 2) Take 5g of the above HY-3 sample and place it in a 20ml beaker, add 2.0ml of a solution in which 0.09g of lanthanum chloride is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 8h; remove the plastic wrap, and dry the sample at 110°C to constant weight. Then, crush the dried sample in a beaker, add 2.0ml of a solution in which 0.15g of diammonium phosphate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 8h; remove the plastic wrap, and dry the sample at 110°C to constant weight; then, calcine the dried sample at 580°C for 5h, with a calcination heating rate of 2°C / min, to obtain catalyst SS-3, with a lanthanum loading of 1.0% and a phosphorus loading of 0.8%.

[0094] Example 4

[0095] The composite catalyst of this embodiment is prepared according to the following method:

[0096] Take 20.00g of SS-1 sample and mix it with 21.42g of kaolin, 56.27g of aluminum sol (Al2O3 mass content 11%), and 8.11g of deionized water, stir evenly and then spray dry and granulate; collect 40-140μm particle samples, calcine at 600℃ for 4h, and the calcination heating rate is 1℃ / min to obtain spherical composite catalyst SS-4.

[0097] Example 5

[0098] The composite catalyst of this embodiment is prepared according to the following method:

[0099] Take 200.00g of SS-2 sample and mix it with 100.00g of cordierite and 66.7g of aluminum sol (Al2O3 mass content 50%), add a small amount of water and stir it into a mud; after the mixture is evenly mixed, extrude it into strips, cut it into small pieces of 0.2-0.5cm, dry it, and calcine it at 600℃ for 4h with a calcination heating rate of 1.5℃ / min to obtain a strip-shaped composite catalyst SS-5.

[0100] Example 6

[0101] The catalyst of this embodiment is prepared according to the following method:

[0102] The preparation method of the catalyst of this embodiment is basically the same as the preparation method of Example 1 (the molar ratio of the raw materials is consistent with that of Example 1), except that in this embodiment, aluminum nitrate is used as the aluminum source, tetraethyl orthosilicate is used as the silicon source, hexamethylenediamine is used as the template, lanthanum sulfate is used as the lanthanum salt, and phosphoric acid is used as the phosphorus salt, with a lanthanum loading of 1.2% and a phosphorus loading of 0.6%, to obtain catalyst SS-6.

[0103] Example 7

[0104] The catalyst of this embodiment is prepared according to the following method:

[0105] In the preparation method of the catalyst of this embodiment, the preparation of the molecular sieve is basically the same as the preparation method of the molecular sieve in Example 2 (the molar ratio of the raw materials is consistent with that in Example 2), except that aluminum chloride is used as the aluminum source and silica sol is used as the silicon source in this embodiment. Then, the method of Example 3 is used to load lanthanum and phosphorus, and the loading amounts of lanthanum and phosphorus are the same as those in Example 3, to obtain catalyst SS-7.

[0106] Comparative Example 1

[0107] The catalyst of this comparative example was prepared according to the following method:

[0108] Take 43.30g of silica sol and dissolve it in 50.00g of deionized water. After stirring evenly, add 0.65g of sodium aluminate. After the sodium aluminate is dissolved, add 4.19g of tetrapropylammonium bromide template. After the template is fully dissolved, slowly add the pre-prepared sodium hydroxide solution (1.38g of sodium hydroxide and 28g of deionized water) dropwise to form a gel. Continue stirring at room temperature for 2h.

[0109] The gel was transferred to a crystallization kettle for crystallization at a temperature of 140°C for 12 hours, and then the crystallization temperature was raised to 180°C for 32 hours. The crystallized product was washed and dried, and calcined at 550°C for 6 hours at a calcination heating rate of 1°C / min to obtain a sodium molecular sieve;

[0110] The sodium molecular sieve was placed in a 1 mol / L ammonium nitrate solution, the amount of ammonium solution was 10 ml (ammonium solution) / g (sodium molecular sieve), and stirred in a water bath at 80°C for 2 hours. The ammonium ion exchange product was centrifuged and washed to complete a single ammonium ion exchange; the ammonium ion exchange was continued, and the above steps were repeated for a total of three ammonium ion exchanges; the sample after the ammonium ion exchange was dried, and then calcined at 550°C for 6 hours, with a calcination heating rate of 1°C / min, to obtain the catalyst DB-1 of this comparative example.

[0111] Comparative Example 2

[0112] The catalyst of this comparative example was prepared according to the following method:

[0113] Take 5g of DB-1 sample and place it in a 20ml beaker, add 2.5ml of 0.24g of lanthanum nitrate solution dissolved in advance, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, dry the sample at 120°C to constant weight; then, calcine the dried sample at 550°C for 6h, and the calcination heating rate is 1°C / min to obtain the catalyst DB-2 of this comparative example, whose lanthanum loading is 1.5%.

[0114] Comparative Example 3

[0115] The catalyst of this comparative example was prepared according to the following method:

[0116] Take 5g of DB-1 sample and place it in a 20ml beaker, add 2.5ml of 0.30g of ammonium phosphate solution dissolved in advance, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and dry the sample at 120°C to constant weight; then, calcine the dried sample at 550°C for 6h, and the calcination heating rate is 1°C / min to obtain the catalyst DB-3 of this comparative example, whose phosphorus loading is 0.9%.

[0117] Comparative Example 4

[0118] The catalyst of this comparative example was prepared according to the following method:

[0119] Take 5g of DB-1 sample and place it in a 20ml beaker, add 2.5ml of 0.33g of lanthanum nitrate solution in advance, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and place the sample at 120°C to dry to constant weight. Then, crush the dried sample in a beaker, add 2.5ml of 0.51g of ammonium phosphate solution in advance, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and place the sample at 120°C to dry to constant weight; then, calcine the dried sample at 550°C for 6h, and the calcination heating rate is 1°C / min, to obtain the catalyst DB-4 of this comparative example, whose lanthanum loading is 2.0% and phosphorus loading is 1.5%.

[0120] Comparative Example 5

[0121] The catalyst of this comparative example was prepared according to the following method:

[0122] Take 5g of DB-1 sample and place it in a 20ml beaker, add 2.5ml of a solution in which 0.24g of lanthanum nitrate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and dry the sample at 120°C to constant weight. Then, crush the dried sample in a beaker, add 2.5ml of a solution in which 0.30g of ammonium phosphate is pre-dissolved, stir evenly, seal the beaker with plastic wrap, and let it stand for 12h; remove the plastic wrap, and dry the sample at 120°C to constant weight; then, calcine the dried sample at 550°C for 6h, with a calcination heating rate of 1°C / min, to obtain the catalyst DB-5 of this embodiment, with a lanthanum loading of 1.5% and a phosphorus loading of 0.9%.

[0123] Test Example 1

[0124] The structures of the catalysts of the examples and comparative examples were characterized, as shown in Table 1.

[0125] Figure 1 The XRD spectra of the catalysts prepared in Comparative Example 1 and Example 1 of the present invention are shown in FIG. Figure 1 It can be seen that Example 1 of the present invention has a typical MFI topological structure, and under the same raw material gel silica-alumina formula conditions as Comparative Example 1, the crystallinity of the catalyst obtained in Example 1 of the present invention is higher.

[0126] Figure 2 NH3-TPD spectra of the molecular sieve catalysts prepared in Comparative Example 1, Comparative Example 4 and Example 1 of the present invention. Figure 2 It can be seen that compared with the samples of Comparative Examples 1 and 4, the acid properties of the catalyst obtained in Example 1 of the present invention are suitable (the temperature of the weak acid site is 203°C and the temperature of the strong acid site is 409°C), which is between that of Comparative Examples 1 and 4, and compared with Comparative Example 1, the proportion of the number of strong acid sites is reduced, and the temperature of the strong acid site is slightly shifted to the left, and the strength of the strong acid center is slightly reduced.

[0127] Figure 3 This is the nitrogen adsorption-desorption curve of the molecular sieve catalyst prepared in Example 1 of the present invention. Figure 3 It can be seen that the nitrogen adsorption-desorption process of the molecular sieve catalyst prepared in Example 1 of the present invention has an obvious hysteresis loop, indicating the presence of mesopores. Figure 4 The DFT model pore size distribution curve of the molecular sieve catalyst prepared in Example 1 shows that the mesopore distribution of the molecular sieve catalyst in Example 1 of the present invention is in two sections of 2-4 nm and 7-20 nm.

[0128] Table 1 Physical properties of different catalysts

[0129]

[0130] Test Example 2

[0131] The catalysts of Examples 1-7 and Comparative Examples 1-5 were tableted at a pressure of 5 MPa, and the tableted samples were crushed and sieved; samples between 20 and 60 meshes were collected and loaded into a fixed bed reactor, and nitrogen was introduced at a gas rate of 50 ml / min; the reactor was heated to 600° C. and activated for 2 h; after the activation, the instrument parameters of the device were adjusted to control the reaction conditions for the catalytic cracking reaction to produce light olefins as follows: reaction temperature 600° C., normal pressure, methanol to oil feed mass ratio of 1:1, oil feed mass space velocity of 2 h -1 , the feed methanol mass concentration is 99.5%. Among them, the oil products are n-hexane, cyclohexane and naphtha. The composition of naphtha is shown in Table 2, and the results after 4 hours of reaction are shown in Table 3.

[0132] Table 2

[0133] Initial distillation point, ℃ 40 Final distillation point, ℃ 172 Normal and iso-alkanes, % (mass) 66.17 Olefins, % (mass) 0.32 Cycloalkanes, % (mass) 31.34 Aromatics, % (mass) 2.17

[0134] Table 3

[0135]

[0136] As shown in Table 3, the catalyst of the present invention has high catalytic conversion performance for alkanes and cycloalkanes, and the conversion rate of the raw materials and the selectivity of the products ethylene and propylene are at a relatively high level. It also has a good catalytic effect on naphtha, the gas production rate (conversion rate) of naphtha is high, and the ethylene and propylene contents in the cracking gas phase products are high.

[0137] Test Example 3

[0138] 1. The spherical catalyst sample SS-4 in Example 4 was loaded into a fixed bed reactor and nitrogen was introduced at a gas rate of 40 ml / min; the reactor was heated to 550° C. and activated for 4 h; after the activation, the instrument parameters of the device were adjusted to control the reaction conditions for the catalytic cracking reaction to produce light olefins as follows: reaction temperature 640° C., normal pressure, methanol to naphtha feed mass ratio of 2:1, naphtha feed mass space velocity of 1 h -1 , the feed methanol mass concentration was 95%. After 4 hours of reaction, the naphtha conversion rate was 93.05%, and the ethylene and propylene selectivity was 59.43%.

[0139] 2. The strip catalyst sample SS-5 in Example 5 was loaded into a fixed bed reactor and nitrogen was introduced at a gas rate of 50 ml / min; the reactor was heated to 650°C for activation for 1 hour; after the activation, the instrument parameters of the device were adjusted to control the reaction conditions for the catalytic cracking reaction to produce light olefins as follows: reaction temperature 550°C, normal pressure, methanol to naphtha feed mass ratio of 0.5:1, naphtha feed mass space velocity of 5h -1 , the feed methanol mass concentration was 50%. After 3.5 hours of reaction, the naphtha conversion rate was 92.37%, and the ethylene and propylene selectivity was 58.93%.

[0140] 3. After the catalyst SS-6 in Example 6 was pressed and sieved, the catalyst was placed in a fixed bed and nitrogen was introduced at a gas rate of 60 ml / min. The reactor was heated to 600°C for activation for 2 hours. After the activation, the instrument parameters of the device were adjusted to control the reaction conditions as follows: reaction temperature 590°C, normal pressure, naphtha feed mass space velocity of 1.5 h -1 After 4 hours of reaction, the naphtha conversion was 93.45%, and the selectivity of ethylene and propylene was 56.27%.

[0141] 4. After the catalyst SS-7 in Example 7 was pressed and sieved, the catalyst was placed in a fixed bed and nitrogen was introduced at a gas rate of 50 ml / min. The reactor was heated to 600°C for 2 hours for activation. After the activation, the instrument parameters of the device were adjusted to control the reaction conditions as follows: reaction temperature 610°C, normal pressure, methanol to naphtha feed mass ratio of 2:1, naphtha feed mass space velocity of 3h -1 , the feed methanol mass concentration is 80%. After 5 hours of reaction, the naphtha conversion rate is 93.51%, and the ethylene and propylene selectivity is 59.33%.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A catalyst for catalytic cracking to produce light olefins, characterized in that: The catalyst comprises an MFI structure molecular sieve and lanthanum and phosphorus loaded on the MFI structure molecular sieve, wherein the mass percentage of the lanthanum in the catalyst is 0.5%-1.5%, and the mass percentage of the phosphorus in the catalyst is 0.5%-0.9%; The catalyst comprises a first mesopore distribution of 2-4 nm and a second mesopore distribution of 7-20 nm; The preparation process of the catalyst is: 1) a gel system including a silicon source, an aluminum source, a polymer stabilizer, a template, deionized water, and a sodium hydroxide aqueous solution is sequentially subjected to a crystallization treatment, a first calcination treatment, an ammonium ion exchange treatment, and a second calcination treatment to obtain a molecular sieve; the mass of the polymer stabilizer is 5-20% of the mass of the silicon source; 2) After the molecular sieve is subjected to lanthanum element loading treatment, an intermediate catalyst is obtained; 3) subjecting the intermediate catalyst to phosphorus loading treatment, followed by drying and third calcination treatments in sequence to obtain the catalyst for catalytic cracking to produce light olefins; The loading treatment of the lanthanum element comprises impregnating the molecular sieve with a lanthanum salt solution, and the impregnation amount of the lanthanum salt solution is 0.2-0.5 mL / g; The phosphorus loading treatment includes impregnating the intermediate catalyst with a phosphorus salt solution, and the impregnation amount of the phosphorus salt solution is 0.2-0.5 mL / g; The crystallization treatment includes a first crystallization treatment and a second crystallization treatment performed sequentially; wherein the temperature of the first crystallization treatment is 120-140° C. and the time is 8-16 hours, and the temperature of the second crystallization treatment is 170-200° C. and the time is 28-40 hours.

2. The catalyst according to claim 1, characterized in that The mesopore volume of the catalyst is 0.08-0.20 cm 3 / g.

3. The catalyst according to claim 1 or 2, characterized in that The micropore volume of the catalyst is 0.08-0.15cm 3 / g.

4. The catalyst according to claim 1, characterized in that The molar ratio of the silicon source, the aluminum source, the sodium hydroxide, the template and the deionized water is 100:(1.11-1.82):(5-12.5):(5-10):(1000-3000).

5. The catalyst according to claim 1 or 4, characterized in that The polymer stabilizer is selected from at least one of polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 6000.

6. A composite catalyst, characterized in that The composite catalyst comprises the catalyst for producing light olefins by catalytic cracking as claimed in any one of claims 1 to 3, and the mass percentage of the catalyst for producing light olefins by catalytic cracking in the composite catalyst is not less than 42%.

7. A method for producing light olefins, characterized in that: The raw material system is catalytically cracked using the catalyst according to any one of claims 1 to 3 and / or the composite catalyst according to claim 6 at 560-640° C. and normal pressure.

8. The production method according to claim 7, characterized in that: The raw material system comprises a first raw material and a second raw material, the first raw material is selected from methanol, the second raw material is selected from at least one of petroleum products with a distillation range of 40-220° C., the mass ratio of the first raw material to the second raw material is 1:1, and the mass space velocity of the second raw material is 1-5h -1 .

Citation Information

Patent Citations

  • Catalytic cracking catalyst and preparation method therefor

    CN103769192A

  • Hierarchical pore Y-type molecular sieve and synthesis method thereof

    CN112850742A